Tocolytic indomethacin: effects on neonatal haemodynamics and cerebral autoregulation in the preterm newborn. Issue 5 (12th March 2013) - Baerts, Willem; van Bel, Frank; Thewissen, Liesbeth; Derks, Jan B; Lemmers, Petra MA
Abstract : Background: Indomethacin has vasoactive properties in cerebral and systemic vascular beds, and it improves cerebral autoregulatory ability. We speculated that tocolytic indomethacin will improve cerebral autoregulatory ability in the very preterm infant in early postnatal life. Methods: Eighteen stable preterm infants gestational age (GA) 25.3–29.6 weeks, birth weight (BW) 660–1430 grams), whose mothers had received 50–150 mg of tocolytic indomethacin within 24 h before birth, and 18 individually matched controls (GA 25.0–29.7 weeks, BW 700–1390 grams) were studied four times for 15 min in the first 24 h of life. Autoregulation was assessed by determining correlations between mean arterial blood pressure (MABP (mm Hg)) and near-infrared spectroscopy-monitored cerebral oxygenation (rScO2 ). Results: MABPs were significantly higher in the indomethacin infants than in the control infants (p=0.03). A decreased ability to autoregulate was found in four of the indomethacin infants, and in six of the control infants, which is not significantly different. Conclusions: Prenatally administered indomethacin, given as a tocolytic in doses of 50–150 mg per day, improved transitional circulation in very preterm infants by significantly raising the MABP. It did not have an effect on the ability to autoregulate the cerebral circulation. In this study, no differences in short-term outcomes, like haemorrhagic or ischaemic cerebral lesions, were observed.